A Study on Mahatma Gandhi NREGA As a Swarozgar Yojana to Help the Poor - Shashikala, Dr. Manoj Sain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
India's number one priority has always been bringing down the poverty rate. In order to combat poverty, the Indian government has begun implementing self-employment projects. Discussions on global economic growth, and particularly the growth of emerging countries, have always included rural development as a central topic. Rural people make up a significant proportion of the population in many emerging nations and certain previously communist states. More over 3.5 billion people call Asia and the Pacific home, with around 63% residing in rural regions. While rural development has helped millions of people in several Asian nations transcend poverty, the vast majority of rural residents still live in abject poverty. There is a lot of strain on the social and economic fabric of many emerging Asian countries due to the growing gap in living standards between rural and urban regions. These and other considerations suggest that rural improvement is crucial. Most governments in emerging markets have recognized the significance of rural development and have been adopting a variety of programs and measures to meet their goals. While some of these nations have achieved amazing accomplishments, others have failed to make a substantial dent in the issue of chronic rural underdevelopment. How the government's strategies to combat poverty and aid in rural development have evolved through time is discussed in this study. The MNREGA is a ground-breaking piece of legislation that is unlike any other program in existence. However, several things need to be stressed so that the true goal of the wage employment programs can be determined. The effects of MNREGA on poverty alleviation, agricultural output, and the pay rate and cost of cultivating field crops throughout the year are discussed in this research.